Topological Aspects of the Design of Nanocarriers for Therapeutic Peptides and Proteins - Nadezhda Knauer; Ekaterina Pashkina; Evgeny Apartsin (MDPI AG, 2019)
Supramolecular chemistry holds great potential for the design of versatile and safe carriers for therapeutic proteins and peptides. Nanocarriers can be designed to meet specific criteria for given application (exact drug, administration route, target tissue, etc.). However, alterations in the topology of formulation components can drastically change their activity. This is why the supramolecular topology of therapeutic nanoconstructions has to be considered. Herein, we discuss several topological groups used for the design of nanoformulations for peptide and protein delivery: modification of polypeptide chains by host-guest interactions; packaging of proteins and peptides into liposomes; complexation and conjugation with dendrimers. Each topological type has its own advantages and disadvantages, so careful design of nanoformulations is needed. Ideally, each case where nanomedicine is needed requires a therapeutic construction specially created for that taking into account features of the administration route, target tissue, or organ, properties of a drug, its bioavailability, etc. The wide number of studies in the field of protein delivery by supramolecular and nanocarriers for proteins and peptides evidence their increasing potential for different aspects of the innovative medicine. Although significant progress has been achieved in the field, there are several remaining challenges to be overcome in future.